Pharmacokinetics Interaction of Non-Steroid Anti Inflammatory Drugs to 99mTc-MDP Radiopharmaceuticals for Bone Imaging and Its Biodistribution - I. Mahendra; I. Daruwati; I. Halimah; S.R. Pajrin (Atom Indonesia, 2018)
99mTc-MDP has been developed as a radiopharmaceutical for bone imaging in nuclear medicine. A drug therapy can alter the pharmacokinetic profiles and biodistribution patterns of radiopharmaceuticals. To achieve an optimum diagnostic outcome, this research focused on pharmacokinetics interaction between two kinds of nonsteroidal anti-inflammatory drugs (NSAID) drugs, meloxicam and sodium diclofenac with 99mTc-MDP using mice(Mus musculus). Therewerefive groups of animal modeland each group consists of three mice except for group II and III which consists of six mice. The groups were classified asuntreated mice (I), mice treated withmeloxicam for 3 days (II), treated with sodium diclofenac for 3 days (III), treated with meloxicam once or at onset (IV), and mice with sodium diclofenac once or at onset (V). Pharmacokinetics interaction and biodistribution test were conducted by injecting 100 µCi/100 µL 99mTc-MDP intravenously. Blood samples were withdrawn from each mouse which were then weighted and counted using single channel analyzer. The %ID/g of 99mTc-MDP in blood of untreated mice (I), mice treated with meloxicam (II) and sodium diclofenac (III) 5 minutes post injection were 3.71, 8.96 and 9.15 % respectively, then decrease to 0.12, 0.01, and 0.01 %, respectively, 24 hours post injection. The results of T-test showed there were no significant differences in distribution of 99mTc-MDP in untreated mice (I) and in treated mice either with meloxicam (II) or sodium diclofenac (III). However, there was significant difference in elimination of 99mTc-MDP in untreated mice (I) and in treated mice either with meloxicam (II) or sodium diclofenac (III). The bone uptakes of 99mTc-MDP were 9.03 ± 0.41, 3.52 + 0.52, 3.62 + 0.45, 8.44 + 1.39, and 8.09 ± 0.86 % in group I, II, III, IV, and V, respectively. T-test showed there were significant differences in bone uptake of 99mTc-MDP in mice with previously treated with meloxicam and sodium diclofenac for 3 days. From these result, it can be concluded that anadministration of meloxicam and sodium diclofenac could accelerate elimination half-life that cause low uptake of 99mTc-MDP radiopharmaceuticalon the bone as the primary target. Therefore, it is necessary to follow up using image study to determine the significance of the effects on image quality.